Prioritizing the First Doses of SARS-CoV-2 Vaccine to Save the Elderly: The Case Study of Italy - Pontrelli, Giuseppe; Cimini, Giulio; Roversi, Marco; Gabrielli, Andrea; Salina, Gaetano; Bernardi, Stefania; Rocchi, Francesca; Simonetti, Alessandra; Giaquinto, Carlo; Rossi, Paolo; Sylos Labini, Francesco (Frontiers in Public Health, 2021)
SARS-CoV-2 is currently causing hundreds of deaths everyday in European countries, mostly in not yet vaccinated elderly. Vaccine shortage poses relevant challenges to health authorities, called to act in a timely manner with scarcity of data. We modelled the mortality reduction of the elderly according to a schedule of mRNA SARS-CoV-2 vaccine that prioritized first dose administration. For the case study of Italy, we show an increase in protected individuals up to 53.4% and a decrease of deaths up to 19.8% in the cohort of over 80s compared to the standard vaccine recalls after 3 or 4 weeks. Our model supports the adoption of vaccination campaigns that prioritize administration of the first doses in the elderly.